Testosterone stimulates growth and secretory activity of the female prostate in the adult gerbil (Meriones unguiculatus) - Santos, Fernanda C. A.; Leite, Rodrigo P.; Custodio, Ana M. G.; Carvalho, Karina P.; Monteiro-Leal, Luiz H.; Santos, Adriana B.; Goes, Rejane M.; Carvalho, Hernandes F.; Taboga, Sebastiao R. (Soc Study Reproduction, 2006)
The prostate of the female gerbil (Meriones unguiculatus) is similar to the human female prostate (Skene gland) and, despite its reduced size, it is functional and shows secretory activity. However, virtually nothing is known about its physiological regulation. This study was thus undertaken to evaluate the behavior of the gerbil female prostate in a hyperandrogenic condition. Adult females received subcutaneous injections of testosterone cypionate (1 mg/kg body weight every 48 h) up to 21 days. Circulating levels of testosterone and estradiol were monitored, and the prostate and ovaries subjected to structural and immunocytochemical analyses. The treatment resulted in sustained high levels of circulating testosterone, and caused a transient increase in estradiol. There was an increase in epithelial cell proliferation accompanied by significant reorganization of the epithelium and an apparent reduction in secretory activity, followed by a progressive increase in luminal volume density and accumulation of secretory products. Immunocytochemistry identified the expression of androgen receptor and a prostate-specific antigen (PSA)-related antigen in prostatic epithelial cells. A circulating PSA-related antigen was also found, and its concentration showed strong negative correlation with circulating estrogen. Epithelial dysplasia was detected in the prostate of treated females. Analysis of the ovaries showed the occurrence of a polycystic condition and stromal cell hyperplasia. The results indicate that testosterone has a stimulatory effect on the female prostate, inducing epithelial cell proliferation, differentiation, secretory activity, and dysplasia. The results also suggest that prostatic growth and activity, polycystic ovaries, and ovarian stromal cell hyperplasia are related to a hyperandrogenic condition in females.
Keywords: androgen receptor; female reproductive tract; ovary; prostate; testosterone